Edukasi Urban Farming Melalui Implementasi Hidroponik dan Budikember Meningkatkan Ketahanan Pangan dan Kesejahteraan Masyarakat di Medan Tuntungan, Sumatera Utara - Siregar, Ameilia Zuliyanti; Nasution, Zulkifli; Tulus, Tulus; Panjaitan, Nismah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Urban farming is carried out to overcome limited land and increase family food security. Cultivating vegetable crops and raising fish are solutions for urban agriculture. The method for implementing International Community Service (PkMI) was implemented in Medan and Penang, Malaysia in June 2024 at the Griya Nusa Tiga Complex Blok B-29 Medan through: a). Socialization and Focus Group Discussion (FGD) regarding urban farming education in residential environments ; b). Hydroponic and Aquaponic training and practice (budikdamber); c). Entrepreneurship training and practice for partners; d). Mentoring and monitoring. PkMI results show ed an increase in the knowledge and skills of partners (20 residents of the Griya Nusa Tiga Complex) in understanding the definition, benefits and implementation of Urban Farming; the growth of the entrepreneurial spirit of residents for independent and sustainable aquaponic cultivation; and able to meet dual protein needs (vegetables and fish); processing budikdamber products appropriately.